2000
DOI: 10.1046/j.1471-4159.2000.0752190.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐Derived Neurotrophic Factor, Neurotrophin‐3, and Neurotrophin‐4/5 Prevent the Death of Striatal Projection Neurons in a Rodent Model of Huntington's Disease

Abstract: Intrastriatal injection of quinolinate has been proven to be a very useful animal model to study the pathogenesis and treatment of Huntington's disease. To determine whether growth factors of the neurotrophin family are able to prevent the degeneration of striatal projection neurons, cell lines expressing brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), or neurotrophin-4/5 (NT-4/5) were grafted in the adult rat striatum before quinolinate injection. Three days after lesioning, ongoing cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(124 citation statements)
references
References 60 publications
3
118
2
1
Order By: Relevance
“…39,40 Neuroprotective strategies using several growth factors have also been proposed for HD. [41][42][43] Among them, BDNF, so far the best candidate, has been shown to modulate the onset and severity of motor and cognitive functions in HD mouse models 5,18,19,44 and to participate in the disruption of the cortico-striatal glutamatergic transmission that occurs in HD. 45,46 Furthermore, transgenic mice overexpressing BDNF in the cerebral cortex, when cross-mated with R6/1 Conditional release of BDNF in Huntington's disease A Giralt et al mice, improve several morphological and behavioral symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 Neuroprotective strategies using several growth factors have also been proposed for HD. [41][42][43] Among them, BDNF, so far the best candidate, has been shown to modulate the onset and severity of motor and cognitive functions in HD mouse models 5,18,19,44 and to participate in the disruption of the cortico-striatal glutamatergic transmission that occurs in HD. 45,46 Furthermore, transgenic mice overexpressing BDNF in the cerebral cortex, when cross-mated with R6/1 Conditional release of BDNF in Huntington's disease A Giralt et al mice, improve several morphological and behavioral symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…29 We have previously shown that BDNF-overexpressing cell lines prevent the death of striatal projecting neurons in a rat model of HD. 43 However, the methodology used in these studies cannot be used for chronic pathologies because of the likelihood of tumor generation by brainimplanted fibroblasts. 47 The use of stem cells in HD cell therapy has also emerged as a powerful tool for the release of striatal neuron protecting neurotrophic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural stem cells are responsive to BDNF, 20,33 and BDNF itself participates in cell differentiation. 112,153 Cortically derived BDNF is an important survival molecule for striatal projection neurons, 123,144 and BDNF is responsive to lesioning of the rodent striatum. 16,26 Reductions in cortical BDNF mRNA 164 and defective transport 60 underlie decreased striatal BDNF and correlate with HD progression in a transgenic mouse model of HD 164,165 and brain tissue in humans with HD.…”
Section: Manipulation Of Endogenous or Exogenous Trophic Factors In Hmentioning
confidence: 99%
“…While the molecular mechanisms by which an expanded polyglutamine tract leads to the selective loss of striatal neurons in HD patients is still to be fully elucidated, attention has been given to endogenously expressed neurotrophic factors known to play a critical role in the development and maintenance of the nervous system, including brain-derived neurotrophic factor (BDNF), [1][2][3][4] glial-derived neurotrophic factor 1,[5][6][7] and ciliary neurotrophic factor [8][9][10][11][12] to provide a broad approach to attenuate neurodegenerative processes.…”
Section: Introductionmentioning
confidence: 99%